2021
DOI: 10.1177/11207000211004862
|View full text |Cite
|
Sign up to set email alerts
|

Modified Dunn procedure versus percutaneous pinning in moderate/severe stable slipped capital femoral epiphyses

Abstract: Background: The modified Dunn procedure (MDP) has risen enthusiasm in treating slipped capital femoral epiphyses (SCFE) due to the anatomic reduction and high patients’ satisfaction rates at long-term follow-up. Main aim of this study is to compare clinical and radiographic outcomes of 2 cohorts with moderate to severe stable SCFE treated by MDP and in situ fixation. Methods: Medical records were analysed to collect demographic data, comorbidities and time from slip to surgery. The collected postoperative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…23,27 The remaining two studies did not show any improvement in clinical outcomes between groups. 24,26 It should be noted that the largest series in our included studies by Galleta et al showed no improvement in clinical outcomes.…”
Section: Clinical Outcomesmentioning
confidence: 79%
See 4 more Smart Citations
“…23,27 The remaining two studies did not show any improvement in clinical outcomes between groups. 24,26 It should be noted that the largest series in our included studies by Galleta et al showed no improvement in clinical outcomes.…”
Section: Clinical Outcomesmentioning
confidence: 79%
“…Four studies were included in the final analysis. [23][24][25][26] These are summarized in Figure 1. All four studies included were retrospective cohort studies, of which only one study enrolled both stable and unstable slips.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations